2018
DOI: 10.1371/journal.pone.0195471
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of three DNA extraction kits on human whole-exome data from formalin-fixed paraffin-embedded normal and tumor samples

Abstract: Next-generation sequencing (NGS) studies are becoming routinely used for the detection of novel and clinically actionable DNA variants at a pangenomic scale. Such analyses are now used in the clinical practice to enable precision medicine. Formalin-fixed paraffin-embedded (FFPE) tissues are still one of the most abundant source of cancer clinical specimen, unfortunately this method of preparation is known to degrade DNA and therefore compromise subsequent analysis. Some studies have reported that variant detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 50 publications
(57 reference statements)
2
44
0
Order By: Relevance
“…There are several studies in the literature that have evaluated QC and DIN/RIN values prior to NGS [11]. Yakovleva etal .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies in the literature that have evaluated QC and DIN/RIN values prior to NGS [11]. Yakovleva etal .…”
Section: Resultsmentioning
confidence: 99%
“…Among others, DNA integrity number (DIN) and RNA integrity number (RIN) from Agilent Technologies, CA, USA, in a range of 1 to 10, give information regarding the fragmentation of the DNA or RNA based on electrophoresis [10,11]. Also, the quality control (QC) value from Illumina, CA, USA, enables the researcher to test the quality of the DNA based on a qPCR, giving values closer to zero when the quality is the highest [12,13].…”
mentioning
confidence: 99%
“…9,17 However, the value of routinely applying UDG treatment to correct artifactual C deamination is open to question: Studies consistently show a limited effect of UDG treatment. Bonnet et al 14 compared C:G > T:A substitution rates in 25 matched FFPE and FF tumor samples using three different FFPE extraction kits, one including and the other two not including UDG treatment. They found that, overall, FFPE samples had 1% higher C:G > T:A substitution rates than FF (presumably the effect of formalin-induced C deamination), but for the FFPE samples, the extraction kit that included the UDG treatment only reduced the substitutions by 0.01%.…”
Section: Formaldehyde-induced Cytosine Deamination and Uracil-dna Glymentioning
confidence: 99%
“…Others have reported use of FFPE DNA in NGS applications [3,[11][12][13][14][15]. Spencer et al compared clinical NGS sequencing data from unpaired FFPE and fresh frozen DNA samples using a capture based approach [3].…”
Section: Discussionmentioning
confidence: 99%